2019
DOI: 10.1101/809962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gamma band oscillations drives information flow in theta and delta band between hippocampus and medial pre-frontal cortex

Abstract: Information flow in the brain is mediated by neuronal oscillations. Prior research has shown that gamma activity considered to be most reflective of neuronal firing is nested within theta cycles. This finding has given rise to the notion that theta phase mediates the gamma oscillations and thereby paces information flow. Such findings have been observed predominantly in cases where the gamma and theta oscillations were measured from the same underlying neuronal substrate. In this article, we analyze the across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Lastly, we have shown that similar to HC coupling dynamics, both cortices exhibit strong coupling between theta/midG and theta/lowG during novelty exploration and the same coupling between delta/beta2 exhibited in HC in the first time window that beta2 exhibited higher power ( Figure 4B and D), these couple is only verified in during the novelty exploration (Figure 4), but not during familiar exploration (SuppFigure B and C) suggesting that the cortical process of information is mostly done during novelty exploration. Similar coupling was previously reported in the mid-prefrontal cortex during recording in freely behaving rodents (Andino-Pavlovsky et al, 2017) or during learning and working memory (Canolty and Knight, 2010;I.b.h, 2019). However, for the first time we show that the local delta oscillations modulate the beta2 not only in the HC, but also in the PAR and mPFC cortices during novelty exploration.…”
Section: -Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lastly, we have shown that similar to HC coupling dynamics, both cortices exhibit strong coupling between theta/midG and theta/lowG during novelty exploration and the same coupling between delta/beta2 exhibited in HC in the first time window that beta2 exhibited higher power ( Figure 4B and D), these couple is only verified in during the novelty exploration (Figure 4), but not during familiar exploration (SuppFigure B and C) suggesting that the cortical process of information is mostly done during novelty exploration. Similar coupling was previously reported in the mid-prefrontal cortex during recording in freely behaving rodents (Andino-Pavlovsky et al, 2017) or during learning and working memory (Canolty and Knight, 2010;I.b.h, 2019). However, for the first time we show that the local delta oscillations modulate the beta2 not only in the HC, but also in the PAR and mPFC cortices during novelty exploration.…”
Section: -Discussionsupporting
confidence: 91%
“…Theta oscillations are thought to coordinate neural networks during memory encoding within and across different areas (Benchenane et al, 2011;Colgin, 2015;Tort et al, 2009). The close relationship between HC and mid-prefrontal areas as it relates to memory encoding and retrieval has been extensively reported (Benchenane et al, 2010(Benchenane et al, , 2011I.b.h, 2019), and theta plays an important role in mediating the function of these two areas (Benchenane et al, 2010(Benchenane et al, , 2011. But until now, no specific oscillatory dynamic responsive to novelty content was reported playing a role in the coordination of different brain areas responsible to process the novelty information.…”
Section: -Discussionmentioning
confidence: 97%